“We Fly Forgotten as a Dream”: A Theology of American Memory in Contemporary Postsecular Literature - Richards, Isaac James (2025)
Via an analysis of Marilynne Robinson’s novel Gilead, Fatima Farheen Mirza’s A Place for Us, and Cormac McCarthy’s No Country for Old Men, I argue that the spiritual nature of memory is a defining feature of contemporary postsecular American literature. I also point out a few key differences between European and American memory, largely by reference to work by Willa Cather and Italo Calvino, to help strengthen my case that American memory specifically is a spiritual and postsecular phenomenon.
Keywords: Postsecularism; Islam; Christianity; Temporality; Spirituality